UV-radiation Dose Assessment for Lexan Track Detector by Using of UV-visible and FTIR Spectroscopy Techniques - Al-Jobouri, Hussain A; Taha, Fala Hatem (Al-Nahrain Journal of Science, 2018)
In the present work, studies the effect UV-radiation dose(1 J/cm²- 360 J/cm²) with power 15 W to Lexan track detector thickness175 µm. Absorbance –A was measured at wavelength 300 nm and 305 nm by using UV-visiblespectroscopy and measure the transmission percent–T% and deviation at the wave number-w 940cm-1 by using Fourier infrared –FTIR spectroscopy. The relationship between the radiation dose of the UV-radiation (J/cm²) and the absorbance-Aat wavelength 300 nm and 305 nm and the wave number-w 940 cm-1 was calculate as a polynomial relation .The present study show that there is a possibility to use the detector Lexan to assessment doses of exposure to UV-radiation in the medical and environmental fields .